Death on the river walk : a Henrie O. mystery - Hart, Carolyn G. (Hart, Carolyn G. Henrie O., 1999)
Pulitzer Prize-winning ex-reporter Henrietta O'Dwyer Collins no longer chases hot stories all over the world, but murderous mysteries seem to find her. This time, a frantic phone call from an old and dear friend on the other side of the world sends Henrie O rushing to San Antonio to check out the baffling disappearance of her friend's devoted granddaughter, Iris Chavez. Iris, employed at the Tesoros Gallery on San Antonio's famous River Walk, has suddenly dropped from sight without a word. Soon Henrie O discovers that amidst the exquisite objects in the prestigious gallery and among the family members is hidden a dark secret--one Henrie O must uncover if she is to find Iris. Late one dark night on the River Walk, Henrie O sees a sprawled body ... and realizes that treachery and disgrace lurk in the shadows of an old and respected business ... and death awaits anyone daring to uncover the truth.